(untitled) (Genta Hredaya: Media Informasi Ilmiah Filsafat Hindu, 2025)
Life in Bali is different from other communities because the majority of the population adheres to Hinduism and passes on many traditions to the next generation, such as the mesuryak tradition in the Bongan Traditional Village in Tabanan sub-district which has been passed down from generation to generation. Based on this, after knowing the problem described, three problem formulations can be made as follows: 1. How is the Mesuryak tradition implemented in the Bongan Traditional Village, Tabanan District, Tabanan Regency?, 2. What is the function of the Mesuryak tradition in the Bongan Traditional Village, Tabanan District, Tabanan Regency? , 3. What is the value of Ethnopedagogy in the Mesuryak tradition in the Bongan Traditional Village, Tabanan District, Tabanan Regency? Research methods refer to the main process carried out by researchers to answer problems, starting from the beginning of the research until data analysis is carried out. This research uses a qualitative descriptive approach with purposive selection of informants. There are four ways to collect data: observation, books, interviews, and documentation. The data triangulation process was used to analyze this research data; Triangulation steps include reduction, presentation, and drawing conclusions. The results of this research will produce research on the process of implementing the Mesuryak Tradition, including: (1). Mesuryak tradition preparation, (2). Time and Place of Implementation of the Mesuryak tradition, and (3). The process of implementing the Mesuryak tradition, as well as the functions in the Mesuryak tradition include: 1). Religious Function, 2). Educational Function, 3). Social Function, and 4). Cultural Preservation Function, 5). Belief Function 6). The function of asking for safety, and the ethnopedagogical values ​​contained in the mesuryak tradition include: (1), Tattwa Educational Values, (2). The Value of Moral Education, (3). Ceremonial Educational Value, and (4). Value of Social Education (5). Value of Religious Education (6). The Value of Bhakti Education.